2021
DOI: 10.3389/fphar.2021.769251
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Adverse Events of Dabigatran Combined With Aspirin in Elderly Patients: An Analysis Using Data From VigiBase

Abstract: Introduction: The elderly are vulnerable to cardiovascular diseases and the incidence of atrial fibrillation (AF) and venous thromboembolism (VTE) increases significantly with age. Dabigatran is a commonly used new oral anticoagulant approved by the FDA for stroke prevention in patients with non-valvular AF and VTE treatment and prevention. Aspirin is commonly used as a preventive drug for cardiovascular diseases. AF and coronary heart disease share many risk factors, so these two diseases often coexist and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The reason may be because of the relatively low actual anticoagulation rate despite the high proportion of patients at high risk in our study. Some studies have indicated that amiodarone, statins, and antibiotics could potentially elevate the risk of bleeding when taken with OACs [31][32][33][34][35][36][37] . However, the limited usage of OAC in the study may cause doctors to overlook the potential bleeding risk caused by drug interactions.…”
Section: Assessment Of Appropriateness Of Ppismentioning
confidence: 99%
“…The reason may be because of the relatively low actual anticoagulation rate despite the high proportion of patients at high risk in our study. Some studies have indicated that amiodarone, statins, and antibiotics could potentially elevate the risk of bleeding when taken with OACs [31][32][33][34][35][36][37] . However, the limited usage of OAC in the study may cause doctors to overlook the potential bleeding risk caused by drug interactions.…”
Section: Assessment Of Appropriateness Of Ppismentioning
confidence: 99%
“…Our team’s previous research also found that 45% (15/33) of the fatal adverse events of dabigatran were related to MEs [ 19 ]. In order to understand the potential risks for the serious MEs reports related to dabigatran, we undertook this study to analyze the clinical characteristics of these cases from the WHO global database of reported potential side effects of medicinal products (VigiBase).…”
mentioning
confidence: 96%